2020
DOI: 10.1002/dta.2890
|View full text |Cite
|
Sign up to set email alerts
|

The complexities associated with new psychoactive substances in influent wastewater: The case of 4‐ethylmethcathinone

Abstract: Consumption of new psychoactive substances (NPS) is an international problem for health, policing, forensic, and analytical laboratories. The transience of these substances in the community, combined with continual slight structural changes to evade legislation makes the elucidation of NPS an analytical challenge. This is amplified in a matrix as complex as wastewater. For that reason, suspect and non-target methodologies, employing high resolution mass spectrometry are the most appropriate current tool to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Over the last decade, the synthesis, trafficking, and use of new psychoactive substances (NPS) have been recognized as a complex global phenomenon. [1][2][3][4][5][6][7][8][9] It is difficult for many countries to monitor and control the development of NPS because of the complexity of its manufacturing, market, and types. 10,11 Moreover, NPS can cause immeasurable harm to users because it is often used in combination with other illicit drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the synthesis, trafficking, and use of new psychoactive substances (NPS) have been recognized as a complex global phenomenon. [1][2][3][4][5][6][7][8][9] It is difficult for many countries to monitor and control the development of NPS because of the complexity of its manufacturing, market, and types. 10,11 Moreover, NPS can cause immeasurable harm to users because it is often used in combination with other illicit drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported the occurrence of SC in wastewaters as influents and effluents, but information about surface waters is scarce [ 13 , 14 , 37 , 38 ]. For instance, 4-MMC (up to 106.00 ng L −1 ), bk-MAP (up to 12.00 ng L −1 ), and MDPV (up to 6.00 ng L −1 ) were measured in influent wastewater samples from eight European countries [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although recent advances in wastewater treatment increased the removal efficiency of hazardous contaminants, some contaminants are still not eliminated or removal rates are low [ 11 , 12 ]. Regarding SC, some studies have already reported their presence in influent samples, but there is little information about their degradation rates, effluents, or environmental levels [ 13 , 14 , 15 , 16 ]. Toxicity effects of NPS, including some SC, have also been reported on aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%